Gender Is a Significant Prognostic Factor for Upper Tract Urothelial Carcinoma: A Large Hospital-Based Cancer Registry Study in an Endemic Area - Huang, Chun-Chieh; Su, Yu-Li; Luo, Hao-Lun; Chen, Yen-Ta; Sio, Terence T.; Hsu, Hsuan-Chih; Lai, Chia-Hsuan (Frontiers in Oncology, 2019)
Introduction: Our hospital is a tertiary medical center located in southern Taiwan, which is an endemic area for upper tract urothelial carcinoma (UTUC) cases. Using a large registry-based surgical database, we examined our cohort of patients with UTUC, and evaluated the treatment outcome and gender-specific differences in this population. Methods: A total of 506 patients with localized UTUC undergoing nephroureterectomy from 2004 to 2013 were enrolled. The patient, tumor, and treatment-related characteristics were prospectively recorded by the registry. Overall (OS) and cancer-specific (CSS) survival outcomes were evaluated as well. Gender differences as related to clinical and pathological factors were examined by chi-square testing. Univariate and multivariate Cox regression analyses were applied. Results: There were more female patients (57.9%) in this population. The median follow-up was 6.9 years for living patients. The actuarial 5-year OS and CSS rates were 69.4% and 84.9%, respectively. Being female, aged <70 years, and early T-stage were statistically significantly associated with better OS and CSS by multivariate analyses. The 5-year CSS rates for females vs. males were 89.6 and 78.5%, respectively (P<0.005). A subgroup analysis suggested that better survival outcomes for females only existed in the stage 0a/0is/I (non-muscle-invasive), but not in the advanced stage. Conclusions: In an endemic area, females were more likely diagnosed with UTUC, but had significantly improved OS and CSS compared to their male counterparts, which were mostly driven by the non-muscle-invasive cases. Future research should focus on better understanding the epidemiologic risk-factor profile and pathophysiologic differences based on gender.